Influence of Optical Basicity on Cu+ Luminescence in Aluminosilicate Oxyfluoride Glasses - Shi, Yafei; Wei, Rongfei; Guo, Junlu; Tian, Xiangling; Hu, Fangfang; Guo, Hai (Frontiers in Materials, 2019)
Cu+-activated aluminosilicate oxyfluoride glasses were successfully synthesized by melt-quenching method in air by adding Al powder as a reducing agent. Their luminescent properties were studied systematically via optical absorption, excitation, and emission spectra. Upon UV irradiation, a blue-emitting band of Cu+ was observed in glass with relatively low optical basicity. By increasing the optical basicity of glass, obvious redshifts of excitation (290 → 313 nm) and emission (435 → 470 nm) peaks were obtained. Through enhancing Cu+ content, the excitation and emission bands presented further redshifts, which shifted from 313 to 338 nm and 470 to 560 nm, respectively. It is proposed that the absorption band and emitting color of Cu+-doped glass can be tuned by changing the optical basicity of glass and Cu+ concentration. The highest quantum yield can reach 62.5%. More importantly, an investigation of the thermal stability showed that over 85% of the room temperature luminescent intensity is preserved at 200°C. These results imply that Cu+-activated aluminosilicate oxyfluoride glasses may be utilized for UV-converted W-LEDs.